What’s Age Got to Do With It? A Comparison of Bariatric Surgical Outcomes Among Young, Midlife, Older and Oldest Adults - Marihart, Cindy L. (Gerontol Geriatr Med, 2016)
Bariatric surgery has become an accepted method to treat obesity and its related diseases in adults; nevertheless, few bariatric surgery follow-up studies compare changes in body mass index (BMI), disease outcomes, and side effects among age groups. This study compares bariatric surgery outcomes across four adult age groups by comparing changes in milestone BMIs such as highest and lowest BMI, perceived existing disease outcomes, and symptoms related to those diseases. Data were obtained using a 40-item questionnaire that was mailed to 2,520 patients of a Midwestern weight management center who were at least 18 months post-bariatric surgical procedure. The 534 respondents were divided into four age groups in years: 18 to 49 (n = 171), 50-59 (n = 148), 60-69 (n = 138), and ≥ 70 (n = 77). There were no differences among the age groups for lowest (p = .93) and current BMI (p = .51). Significant improvement in eight chronic diseases occurred across all age groups. There were no differences between age groups in reported occurrence of incontinence (p = .65), diarrhea (p = .22), flatulence (p = .46), heartburn (p = .73), and indigestion (p = .22). Constipation rarely occurred among the oldest adults (p < .001). Bariatric surgery should be considered an option for weight loss and disease management for older adults as much as it is for younger adults.